Functional fitness and nutritional status of institutionalized elderly - Honório, Samuel (2017)
BACKGROUND: Measuring the functional fitness is essential to provide a working basis for assessing and prescribing exercises. There is a special interest in developing procedures and tests able to provide reliable information and general vocabulary for researchers and practitioners. We intend with this study to analyze the functional fitness of different groups of institutionalized elderly of both genders, relating it with their nutritional status. METHODS: A sample of 46 participants, 31 males and 15 females aged between 65 to 93. For this investigation, the Mini Nutritional Assessment (MNA) was used in order to categorize the nutritional status with a Mediterranean diet that was used. For the assessment of the functional fitness, it the battery Fullerton Functional Fitness Test (FFFT) developed in 1999 by Rikli and Jones was used. RESULTS: We found that the elderly who maintained a diet divided into seven meals had more favorable values in all categories of the battery tests with significant differences. We also found that the nutritional status of the elderly and the number of meals is statistically significant in tasks measuring strength, agility and aerobic capacity. CONCLUSIONS: The elderly with normal nutritional status have better performance in the battery tasks, particularly those who choose the diet divided into seven daily meals. The Mediterranean Diet used seems to be favorable in this population, in both genders and it promotes the maintenance of their physical abilities.